Peningkatan Kuat Tekan Bebas (UCS) Tanah Lempung (CH) Terhadap Penambahan Semen Dan Limbah Fly Ash (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
High plasticity clay is categorized as soft soil which has low strength and bearing capacity, high compressibility and large shrinkage, so that to increase strength and improve bearing capacity it is necessary to make stabilization efforts on the soil. The stabilization effort carried out in this study was mixing of additives in the form of fly ash and cement. The method used was a laboratory experimental method by testing UCS samples. The sample mix that has been made was varied based on curing days, namely 0 days, 7 days and 28 days with variations of cement mixture 3%, 5% and a mixture of fly ash 5%, 10%, and 15%. A sample naming method is also provided to make it easier to summarize the results of each planned test variation. Based on the test results, the addition of cement and fly ash increases the value of free compressive strength (Cu) and compressive strength (qu). The highest increase in UCS occurred in soil with 5% cement and 15% fly ash with 28 days curing. The increase in qu in the UCS sample is the largest in the variation of the sample T0-S5-FA15-C28 with a value of 218.41 kPa, this increase is 89.91% when compared with the qu TA value of 22.04 kPa. Keywords: Cement, Fly Ash, UCS.